Representasi Gaya Hidup Konsumtif Generasi Muda Pada Meme “Lambang Baru Kemapanan” - Azmi, Rayhan Muhammad; Astuti, Sri Wahyuning (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
The young generation is considered to have and implement consumer lifestyle practices that have indirectly harmed them. This consumer life then received criticism for using memes as a medium. The research method used is Norman Fairclough's critical discourse analysis by implementing the 3 dimensions of critical discourse analysis and then analyzing it using Norman Fairclough's "4 steps of social wrong" method to be able to find solutions to social irregularities that occur in society. This research aims to look at the representation that the "new symbol of the establishment" meme is trying to show in the lifestyle of the younger generation today by dissecting it through the dimensions of text, discursive practices and socio-cultural praxis. The results obtained from this research are that many young people practice consumerism just to increase their social status. Apart from that, peer pressure occurs in the social environment, forcing them to buy things beyond their means. This research concludes that the criticism made by the sltyhub Instagram account also represents the social reality conditions of the younger generation, especially the practice of consumerism to improve their social status.